Intraspecific shell-shape variation in the razor clam Ensis macha along the Patagonian coast - Marquez, Federico (2011)
Ensis macha has a wide distribution along the Pacific and Atlantic southern coasts of South America. The pattern of morphological shell variation of this razor clam was analysed in 12 populations sampled along its whole Atlantic distribution, covering a latitudinal range of 3,700 km. The southernmost extant population of E. macha was recorded in the Beagle Channel. Variation in shell outline was assessed using elliptic Fourier analysis of adult individuals followed by different multivariate analyses. Significant shell-shape variation was found along the latitudinal range. Elliptical Fourier analysis revealed that trends in shell slenderness and curvature were associated mainly with salinity and water depth of the localities. Each locality presented a distinct shell shape, different from all other localities. Nevertheless, the populations could be grouped into four large assemblages between which a latitudinal gradient of shell shape was observed. Phenotypic divergence in shell shape is suggestive of population differentiation, but assessing the underlying processes is not straightforward because of the complex interaction between genetic and environmental factors. The possible evolutionary processes that mediate the effects of environmental variables and geographical distances on the shell-shape variation are discussed.